NUTRIENT CONTENTS OF 140 RUGGERI ROOTSTOCK CANES IN DORMANT SEASON - C. Türkmen; A. Dardeniz; N. M. Müftüoğlu; Z. Gökbayrak; A. Kabaoğlu (Journal of Animal and Plant Sciences, 2011)
This research was carried out to ascertain if there were significant differences in the mineral contents of 140 Ruggeri (140 Ru) canes collected during dormant period. Cuttings of the rootstock 140 Ru prepared for propagation of grafted grapevines were profiled for their mineral contents during two dormant seasons. Cuttings were sampled at four different times starting from leaf fall and divided into five sections. Mineral content changes in the dormant season and along the length of the canes were found to be significant to a limited extent (P value=0.05). The results showed that mineral content in 140 Ru rootstock canes slightly varied with sampling time and sampling section.
Keywords: Grapevine; rootstock; cutting; minerals; 140 Ruggeri.